2001
DOI: 10.1007/s004280100525
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of E-cadherin in chordomas: diagnostic marker and possible role of tumor cell affinity

Abstract: Chordoma is a relatively rare malignant bone tumor thought to arise from the remnants of the fetal notochord. Chordomas express epithelial cell markers such as cytokeratin and epithelial membrane antigen (EMA), which strongly suggests that the tumor cells grow via the mechanism of epithelial characterized cell-cell interactions. However, there are no known reports that have studied epithelial characterized cell-adhesion molecules such as E-cadherin or epithelial cell adhesion molecule (Ep-CAM) in chordomas. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
13
2
Order By: Relevance
“…As shown in Figure 1A-1C, ET-1 induced wound healing (Figure 1A), migration (Figure 1B) and invasion (Figure 1C) of chondrosarcoma cells in a dose-dependent manner. The essential features of EMT in the context of tumor progression are enhanced cell migration and invasion [17, 18]. To examine whether ET-1 is required for EMT in chondrosarcoma, the chondrosarcoma cell lines were treated with ET-1.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1A-1C, ET-1 induced wound healing (Figure 1A), migration (Figure 1B) and invasion (Figure 1C) of chondrosarcoma cells in a dose-dependent manner. The essential features of EMT in the context of tumor progression are enhanced cell migration and invasion [17, 18]. To examine whether ET-1 is required for EMT in chondrosarcoma, the chondrosarcoma cell lines were treated with ET-1.…”
Section: Resultsmentioning
confidence: 99%
“…While not a specific aim of this study, the identification of these positive and negative notochordal markers may also be helpful to understand the biology of chordomas …”
Section: Discussionmentioning
confidence: 99%
“…The same study showed that the expression of E-cadherin was decreased and correlated with increased mortality. These findings suggest that the cadherins play a crucial role in the malignancy of chordomas [41,60,65,66,104].…”
Section: Invasion and Metastasismentioning
confidence: 99%